PENGARUH MACAM NUTRISI TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS KEDELAI YANG DIKEMBANGKAN SECARA WICK SYSTEM PADA LAHAN TERDAMPAK ROB: Kata kunci: hidroponik, nutrisi, kedelai, varietas, wick sistem. - ubad badrudin; sajuri; syakiroh jazilah; Komala Ardiyani; muhammad asfindra saksono; Eka Adi Supriyanto (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
The research aims to determine the effect of various nutrients on the growth and production of several soybean varieties developed using the vertigation wick system method on land affected by tidal floods and their interactions. The research was conducted in Klidang Wetan Village, Batang Subdistrict, Batang Regency from March to June 2021 at an altitude of 5 meters above sea level. The experimental design used was Split Plot consisting of 2 factors with 3 replications. The first factor is the type of nutrients (N) as the main plot (N0 = Control, N1 = AB Mix, N2 = Phonska Fertilizer, N3 = NPK Mutiara) and the second factor is the variety (V) as a sub plot (V1 = Anjasmoro variety, V2 = Deja 1 variety, V3 = Dega 1 variety). Data were analyzed with the F test, if significantly different followed by LSD 5%. Variables observed were plant height, number of leaves, leaf area, longest root length, stem diameter, plant fresh weight, total volume of nutrients, number of active root nodules, pod weight per plant, number of pods per plant, and root volume. The results showed that the types of nutrients differed significantly on the number of leaves, leaf area, longest root length, plant fresh weight, and pod weight per plant. The best nutrition was achieved in the AB Mix treatment. Varieties differed significantly on the total volume of nutrients, the number of active root nodules and root volume. The best results were achieved in the Deja1 variety treatment. The interaction between nutrients and varieties was not significantly different on all observation variables.